1999
DOI: 10.1002/(sici)1097-4636(199908)46:2<245::aid-jbm14>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of bovine serum albumin in calcium phosphate coating on titanium

Abstract: Calcium phosphate (Ca-P) and bovine serum albumin (BSA) were coprecipitated as a coating on commercially pure titanium (cpTi) with a high protein loading (15 wt %) by employing a recently developed wet-chemistry technique. It was observed that the incorporation of BSA significantly modified the morphology, composition, and crystallinity of the Ca-P coating. The Ca-P coating without BSA is a mixture of hydroxyapatite (HA) and octacalcium phosphate (OCP) with sharp-edged thin OCP crystal plates on the top layer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 36 publications
7
94
0
2
Order By: Relevance
“…836 Biocomposites of CDHA with water-soluble proteins, such as BSA, might be prepared by a precipitation method. 561,[839][840][841][842] In such biocomposites, BSA is not strongly fixed to solid CDHA, which is useful for a sustained release. However, this is not the case if a water/oil/water interfacial reaction route has been used.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…836 Biocomposites of CDHA with water-soluble proteins, such as BSA, might be prepared by a precipitation method. 561,[839][840][841][842] In such biocomposites, BSA is not strongly fixed to solid CDHA, which is useful for a sustained release. However, this is not the case if a water/oil/water interfacial reaction route has been used.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Biocomposites of CDHA with water-soluble proteins, such as bovine serum albumin (BSA), might be prepared by a precipitation method [463,[689][690][691][692]. In such biocomposites, BSA is not strongly fixed to solid CDHA, which is useful for a sustained release.…”
Section: Biocomposites With Collagenmentioning
confidence: 99%
“…Wen et al pretreated titanium by acid etching, boiling diluted alkali incubation, precalcification, and immersed it in SCS with or without containing BSA. Their results also showed that the incorporation of BSA significantly modified the morphology, composition, and crystallinity of the apatite coating (Wen et al, 1999). The release rate of Ca 2+ ions from these BSA-containing apatite layers was slower than from non-protein-containing ones within the bathing medium, which indicated that BSA bonded strongly to Ca 2+ ions within the crystal lattice.…”
Section: Effects Of Protein Addition In Simulated Body Fluid On Biomimentioning
confidence: 99%
“…By this technique, biologically active molecules can be coprecipitated with apatite crystals onto metal implants rather than being merely adsorbed on its surface(Y. Liu et al, 2001Liu et al, , 2003Liu et al, , 2006Wen et al, 1999). Therefore, the biomimetic apatite coating can be used as the carriers for biologically active molecules.…”
Section: Effects Of Protein Addition In Simulated Body Fluid On Biomimentioning
confidence: 99%